The involvement of α‐proteobacteria Phenylobacterium in maintaining the dominance of toxic Microcystis blooms in Lake Taihu, China. (10th November 2020) - Zuo, Jun; Hu, Lili; Shen, Wei; Zeng, Jiaying; Li, Lin; Song, Lirong; Gan, Nanqin
Summary: Lake Taihu in China has suffered serious harmful cyanobacterial blooms for decades. The algal blooms threaten the ecological sustainability, drinking water safety, and human health. Although the roles of abiotic factors (such as water temperature and nutrient loading) in promoting Microcystis blooms have been well studied, the importance of biotic factors (e.g. bacterial community) in promoting and meditating Microcystis blooms remains unclear. In this study, we investigated the ecological dynamics of bacterial community, the ratio of toxic Microcystis, as well as microcystin in Lake Taihu. High‐throughput 16S rRNA sequencing and principal component analysis (PCA) revealed that the bacteria community compositions (BCCs) clustered into three groups, the partitioning of which corresponded to that of groups according to the toxic profiles (the ratio of toxic Microcystis to total Microcystis, and the microcystin concentrations) of the samples. Further Spearman's correlation network showed that the α‐proteobacteria Phenylobacterium strongly positively correlated with the toxic profiles. Subsequent laboratory chemostats experiments demonstrated that three Phenylobacterium strains promoted the dominance of the toxic Microcystis aeruginosa PCC7806 when co‐culturing with the non‐toxic PCC7806 mcyB − mutant. Taken together, our data suggested that the α‐proteobacteria Phenylobacterium may play a vital role in the maintenance of toxic Microcystis dominance in Lake Taihu.